THE INFLUENCE OF THE USE OF INFORMATION AND ORGANIZATIONAL COMMUNICATION TECHNOLOGY ON THE PERFORMANCE OF VILLAGE APPARATUS IN PASIR DISTRICT EAST LAMPUNG SAKTI - Aliyah, Hikmatul; Buchori, Buchori; Anhari, Ahmad (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
For the development of public services, government organizations need to be able to create and enhance services. Resources are necessary for all organizations, including governmental and commercial ones, to accomplish their objectives. One organizational resource that is essential to reaching shared objectives is human resources. The public expects the government to provide quality services. Performance evaluations are given to employees. Village authorities in the Pasir Sakti District of East Lampung are among the staff members whose work is evaluated and in need of improvement in order to promote organizational performance. The degree of service provided by village government personnel is measured by their performance. "The Influence of Organizational Information and Communication Technology on the Performance of Village Officials in Pasir Sakti District, East Lampung" is the research's stated goal. Since the research is given as statistics, the author in this instance used a quantitative approach to perform the study. Keywords: Information Technology, Organizational Communication, Employee performance